2010
DOI: 10.1097/brs.0b013e3181d83538
|View full text |Cite
|
Sign up to set email alerts
|

Video-Assisted Thorascopic Repair of a Subarachnoid-Pleural Fistula in a Child After Thoracic Tumor Resection

Abstract: VATS technique should be considered for a safe, efficacious, and durable CSF leak repair and as an alternative to open thoracotomy in the pediatric age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…β2‐transferrin could not be measured in the present patient. The diagnosis of a CSF fistula was confirmed with MRI and CT. CT myelography, MR cisternography and MR myelography can be used for identifying anatomical detail 1,5 . In the present case, fistula localization was determined by MRI and CT myelography.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…β2‐transferrin could not be measured in the present patient. The diagnosis of a CSF fistula was confirmed with MRI and CT. CT myelography, MR cisternography and MR myelography can be used for identifying anatomical detail 1,5 . In the present case, fistula localization was determined by MRI and CT myelography.…”
Section: Discussionmentioning
confidence: 74%
“…Intervention is almost always required because subarachnoid‐pleural fistulas do not resolve with conservative therapies 1 . Previously reported conservative therapies consist of lumbar/cervical spinal catheter or passive CSF drainage by the chest tube, positive pressured non‐invasive ventilation, serial thoracentesis, epidural blood patch or fibrin glue insertion and bed rest 6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 There are few reports of SPF in the pediatric neurosurgical literature, with sporadic single cases that mainly occur after thoracic tumor resection and trauma. 9,10,18,24 Common to these cases were requirements for open surgery and repair of the dural defect. Postoperatively, patients in these cases remained in the hospital for 7-14 days for observation and chest tube management.…”
Section: Discussionmentioning
confidence: 99%
“…20 Surgical intervention is often required to eliminate this pressure differential and entails direct repair of pleural and dural defects, either with open surgery or in a minimally invasive fashion. 10,20 This surgical intervention most commonly requires the use of a dural substitute or sealant (Tisseel, DuraSeal) and can be augmented with a vascularized graft. 7,8,19 Other authors have reported success with secondary occlusion of fistulas by using an epidural blood patch (EBP) 1 or synthetic material such as DuraSeal, Tisseel, and even Onyx; 4,6,11 however, all of these successes occurred in adult patients.…”
Section: Discussionmentioning
confidence: 99%